Efeito da via de sinalização slam sobre células T na resposta in vitro à leishmania braziliensis - Coelho, Zirlane Castelo Branco (2011)
Immune cells activation is modulated by balancing the signals triggered by a variety of cell surface receptors, including receptor activators, co-stimulating receptors and inhibitory receptors. Receptor-related signaling molecule in lymphocyte activation (SLAM) influences the immune cell activation. In this study we investigated the role of SLAM in immune response of cutaneous leishmaniasis caused by L. braziliensis, as well as if the response of individuals high (HP) or low (LP) IFN-γ producers is modulated by SLAM signaling pathway. Peripheral blood monocuclear cells (PBMC) isolated from 43 health individuals were cultured in vitro with anti-SLAM, rIFN-γ, rIL-12 and phytohemagglutinin in the presence or in the absence of L. braziliensis. It was found that L. braziliensis promoted a significantly reduced SLAM expression in T cells, after 120 h of cultured, possibly indicating activation of this pathway in the initial immune response. SLAM expression behaved differently in HP and LP groups. In LP group, L. braziliensis did not modify SLAM expression in T cells in early immune response. The effect of anti-SLAM on SLAM pathway reduced the expression of this protein in the early stages of the immune response of PBMC stimulated with L. braziliensis. After 120 h the effect of anti-SLAM did not alter CD3+SLAM+ expression in both groups. The proinflammatory cytokines, rIFN-γ and rIL-12, present in the microenvironment with L. braziliensis, reduced SLAM expression only in HP group after 6 h of culture and did not change this response after 120 h. Anti-SLAM at a concentration of 10 μg/ml presented no effect on production of cytokines IFN-γ and IL-13 in both groups, but significantly increased IL-10 production in the HP group. Furthermore anti-SLAM associated with L. braziliensis and rIFN-γ simultaneously did not modify IFN-γ, IL-13 and IL-10 productions. Anti-SLAM associated with L. braziliensis and rIL-12 simultaneously induced an increase of IFN-γ in LP group, and increased IL-13 in HP group. These results suggest that in vitro immune response of PBMC exposed to L. braziliensis, the SLAM signaling pathway acts in modulating Th1 response in HP group and induces a condition of temporary immunosuppression in LP group, not previously described in literature.